Two Access databases organization for Sasa lead-zinc deposit and tailings, Republic of Macedonia - Serafimovski, Dalibor; Gicev, Vlado; Mitreski, Kosta (STEF92 Technology Ltd, 2014)
Within the Republic of Macedonia there are numerous polymetallic mineral deposits important for its economy. This paper focuses on efforts we made to organize Microsoft Access database with the most representative data for the most important Pb-Zn deposit in the Republic of Macedonia, the Sasa deposit and mine near the city of Makedonska Kamenica. First of all, with the software package “Microsoft Access” we have organized database with information of the most important geological, metallogenic and economic features of the deposit. Also, we have not omitted the fact that each active mine exploitation has been followed with production of significant anthropogenic input to the environment, so we have structured and anthropogenic database too. Both databases were adapted for simple and sophisticated querying of particular deposit and anthropogenic features and allows edition of reports and a geographic display of the queried information.
Keywords: mineral deposit, Access database, reserves, anthropogenic concentrations